Competitiveness of Regional Agri-Food Systems: A Theoretical Review - Neganova, Valentina P.; Chistiakov, Yury F.; Drokin, Veniamin V.; Zhuravlev, Aleksey S.; Sedelnikov, Vladislav M. (Economy of Regions, 2021)
Numerous interpretations of the competitiveness of regional agri-food system in the scientific literature are predominantly fragmentary depending in specific goals of research. This creates problems for universalizing approaches, identifying areas of their complementarity, and integrating new definitions. To systematize existing interpretations of the competitiveness of regional agri-food systems and identify new areas of research, we carried out a structured review of the scientific publication from peer-reviewed academic journals indexed in international and Russian databases. We applied the method of content analysis to identify the definitions of the “competitiveness”, “sustainable competitiveness”, “regional agri-food systems”. Moreover, we calculated the average percentage of journal articles mentioning these categories per year. Cluster analysis of journal articles allowed identifying general concepts of the competitiveness of regional agri-food. As a result we systematized the definitions of the concept of «competitiveness of regional agri-food systems» depending on research area, actors and the level of sustainability of competitiveness. The systematization and classification of research investigating the competitiveness of regional agri-food systems enabled determining new areas of future research. Firstly, a more detailed analysis of the factors of the sustainable competitiveness of regional agri-food systems, particularly in pandemic and post-pandemic periods is of critical importance. Secondly, searching for a comprehensive toolkit for ensuring sustainable competitiveness of regional agri-food systems, as well as cooperation and competition among the agri-food companies in the Internet can be a focus for future research.